ANALISIS PELAKSANAAN DAN MOTIVASI PENYULUH PERTANIAN DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Nurhadi Susanto; Rosnita Rosnita; Eri Sayamar (UIR Press, 2015)
The aims of this research are to learn the implementation of agricultural extension and to analyze the internal and external motivation of agricultural extension staff in Kubu district of Rokan Hilir regency. This research was conducted in Kubu district of Rokan Hilir regency by using survey method. The population of this research is the entire extension officers. A total of 8 persons of the population was taken as respondent as census. The first goal of this research was analyzed by using a descriptive qualitative method and the second and third goals were analyzed by using Likert Scale's Summated Rating (SLR). The results indicate that the implementation of agricultural extension in the Kubu district run under the porch of agricultural extension which was carried out by eight extension staff who built 15 villages and 117 farmer community. The internal motivation of agriculture extension staff is in the